PERANAN KEPOLISIAN SATUAN LALU LINTAS DALAM MENANGANI TINGGINYA TINGKAT PELANGGARAN LALU LINTAS OLEH KENDARAAN BERMOTOR DIWILAYAH HUKUM POLISI RESORT KUANTAN SINGINGI - Tri Berlian Hotanices (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Singingi Kuantan town. Traffic violations by motor vehicles from the year 2011-2012 hasincreased quite rapidly. Therefore the traffic police as an agency that is authorized to regulatetraffic, has made various efforts in tackling traffic violations. One of them with the preventivemeasures early prevention of police traffic violations committed by motor vehicle, conductcounseling about traffic and alert the public about the importance of respect the traffic signs andbanners put up relating to the traffic. While the repressive efforts is an action taken by lawenforcement officers in the aftermath of a crime or offense. that is by giving warning andenforcement action with a traffic ticket. Enforcement action was conducted by the police trafficunit for traffic violations committed by motorists. Traffic police in performing their duties subjectto the traffic laws. However, the role of the traffic police in dealing with high levels of perceivedtraffic violation is less than optimal, especially the region of the police law Kuantan resortSingingi this is because there are still many obstacles facing the traffic police in performing theirduties as law enforcement especially in the field of traffic., Such as the lack of quality and quantityof traffic police, to lack of facilities and infrastructure, as well as the lack of traffic policepersonnelKey Word: Role - Traffic Police - Traffic Violations